Characterization of X-Chromosome Gene Expression in Bovine Blastocysts Derived by In vitro Fertilization and Somatic Cell Nuclear Transfer - Min, Byungkuk; Park, Jung Sun; Jeon, Kyuheum; Kang, Yong-Kook (Frontiers in Genetics, 2017)
To better understand X-chromosome reactivation (XCR) during early development, we analyzed transcriptomic data obtained from bovine male and female blastocysts derived by in-vitro fertilization (IVF) or somatic-cell nuclear transfer (SCNT). We found that X-linked genes were upregulated by almost two-fold in female compared with male IVF blastocysts. The upregulation of X-linked genes in female IVFs indicated a transcriptional dimorphism between the sexes, because the mean autosomal gene expression levels were relatively constant, regardless of sex. X-linked genes were expressed equivalently in the inner-cell mass and the trophectoderm parts of female blastocysts, indicating no imprinted inactivation of paternal X in the trophectoderm. All these features of X-linked gene expression observed in IVFs were also detected in SCNT blastocysts, although to a lesser extent. A heatmap of X-linked gene expression revealed that the initial resemblance of X-linked gene expression patterns between male and female donor cells turned sexually divergent in host SCNTs, ultimately resembling the patterns of male and female IVFs. Additionally, we found that sham SCNT blastocysts, which underwent the same nuclear-transfer procedures, but retained their embryonic genome, closely mimicked IVFs for X-linked gene expression, which indicated that the embryo manipulation procedure itself does not interfere with XCR in SCNT blastocysts. Our findings indicated that female SCNTs have less efficient XCR, suggesting that clonal reprogramming of X chromosomes is incomplete and occurs variably among blastocysts, and even among cells in a single blastocyst.